A LOOK INTO THE EMPHASIS PHYSICIANS, VETERINARIANS, AND PREGNANCY EDUCATORS PLACE ON PROVIDING TOXOPLASMOSIS INFORMATION FOR PREGNANT PATIENTS OR CLIENTS - Timmins, Caitlin (My University, 2015)
The mission of the Hunterdon County Health Department is to ensure the health and safety of the public. The purpose of the following paper is to discuss the knowledge and emphasis human and veterinary medical professionals place on educating patients and clients about toxoplasmosis. Toxoplasmosis is caused by a parasite that commonly affects both people and animals. This paper discusses the knowledge of health professionals about toxoplasmosis and the recommendations they make to pregnant clients about toxoplasmosis testing and ways to prevent transmission. A total of 17 veterinarians, 10 physicians, and 6 pregnancy educators responded to a survey regarding toxoplasmosis. The emphasis that health professionals place on discussing the risks of toxoplasmosis transmission with pregnant clients varies over a wide range. The results of this project confirm that most physicians and veterinarians discuss toxoplasmosis with patients and clients; however, a smaller percentage of pregnancy educators do so. Pregnancy educators also place a lower priority on such discussion than do physicians and veterinarians. The data support the fact that health professionals believe patients and clients have a low awareness of toxoplasmosis and its hazards. Knowledge about toxoplasmosis among health professionals is mixed at best with veterinarians having the most complete working knowledge. The survey results support strongly the need for educational tools for use in communicating the risks of toxoplasmosis to patients and clients.
Keywords: Toxoplasmosis; T gondii; Pregnancy; Oocyst; Parasite; Cat; Public Health (0573)